My Dog, My Hero - Betsy Byars, Betsy Duffey and Laurie Myers (New York, United States Henry Holt & Company, 2000)
There's Smiley, who fought a giant bull. Bear used his giant paws to save the life of another dog. Munchkin warned a gardener of a poisonous snake about to strike. Old Dog helped find people buried under rubble after a tornado. Buster pulled a baby carriage out of the path of a careening truck. Blue, who had never been known to bark, used his voice to bring help to his wounded master. Dopey's constant barking saved the life of a baby left in a sweltering car. Little Bit brought love and companionship to a nursing home residen
Keywords: Junior Fiction Junior Library